Which expression is equivalent to (3a)-2
2 answers:
Answer:
removing of bracket
Step-by-step explanation:
(3a)-2
3a×(-2)
-6a
Answer:
1/9a2
Step-by-step explanation:
I'm not sure if there's supposed to be a list of answers, but 1/9a2 is one. Hope this helps! Let me know if there was supposed to be a list.
You might be interested in
Answer:
not sure man... goodluck tho
Well 1/3 for savings means that you save 1/3*4500 or 1500 dollars. You then have $3000 left. Of this if you spend 50% on food, you spend 0.5*3000 or 1500 dollars on food.
h=9 A=((a+b)/2)h 234=((32+20)/2)h 234=(52/2)h 234=26h 9=h
Answer:
-1, -7, -13, -19
Step-by-step explanation:
-2(-3)-7 =6-7= -1
-2(0)-7 =0-7= -7
-2(3)-7 =-6-7= -13
-2(6)-7 =-12-7= -19
Ah clever. So you need two formulas. 1) Volume of the marble. 4(pi)r^3/3 = 4(pi)(1.4)^3/3 <span>= 11.49 (approx) </span> 2) Formula for density. D = M / V = 9 / 11.49 = 0.78 0.78 < 1 Therefore the marble will float.